Drone-based foliar nutrient spray improves physiology, nutrient uptake and yield of greengram (Vigna radiata) - T RAMESH; K DAYANA; S RATHIKA; S PAZHANIVELAN (The Indian Journal of Agricultural Sciences)
The present study was carried out during summer 2021 to optimize the spray volume and nutrient concentration for drone application of nutrients to accelerate the physiological growth, nutrient uptake and productivity of greengram. The experiment was conducted in randomized block design (RBD) with 7 treatments, replicated thrice. Treatments consisted of 1% and 2% nutrient solution (TNAU Pulse wonder), two levels of spray volume (30 and 50 litre/ha) for drone application, manual spray (500 litre/ha spray volume) and control. The results showed that foliar application of nutrients through drones in greengram at flowering stage increased the physiological growth, nutrient uptake and yield over manual spray. Spray fluid used in the drone at 30 and 50 litre/ha was statistically comparable with each other, indicating that 30 litre/ha is sufficient for nutrient spray. When compared to 500 litre/ha spray fluid under manual spray, the drone used only 30 litre, with a reduction of 470 litre/ha (94%). However, the concentration has to be increased from 1–2% under drone application to have a significant effect. From the present study it may be concluded that drones could be effectively used for foliar application of Pulse wonder 2% with spray volume of 30 litre/ha at flowering stage, for better plant physiological activities, nutrient uptake and yield of greengram under the current scenario of labour scarcity in agriculture.